Embodied Experience of Gender and Self in Transnational Migration from Nepal - Dahal, Kapil Babu (Patan Prospective Journal, 2023)
In their efforts to seek employment and income abroad, these days, people leave their place of origin and move to new places through transnational migration. In that sense, transnational migration can be taken as liberating or escaping from the existing context. While looking at certain inherent procedures of transnational migration, it can be questioned whether people can escape from their social and cultural web and conditions through this process. In this sense, transnational migration reinstates and reflects prevailing social norms and values concerning gender, class, and well-being. On top of this, based on ethnographic information, this paper also highlights the process that reflects their embodied experience of border crossing, and thus transnational migration embodies the process of gender and a particular kind of self.